RADI-11. THREE CASES OF CLINICALLY SUSPECTED CAVERNOMAS FOUND TO HAVE VERY DIFFERENT PATHOLOGIES. Issue 2 (22nd June 2018) - Pytel, Nicholas; Harn, Nicholas; Salamat, Shahriar M; Bradley, Kristin; Ahmed, Raheel; Iskandar, Bermans; Puccetti, Diane
Abstract: Often radiological imaging is relied on for initial guidance as to the cause of different central nervous system symptoms such as headaches, neurological deficits, or other neurological changes. The clinical presentation is used along with the neurological imaging to provide the first steps for management in central nervous system lesions, including optimal timing for surgical procedures as indicated. We present 3 pediatric cases where the initial neurological imaging and clinical presentation appeared consistent with cavernoma or cavernous angioma, however, surgical pathology found that in all 3 cases, more concerning lesions were found beyond the vascular component. A 7 year old boy with obstructive hydrocephalus thought to be caused by vascular pineal cavernoma was later found to be a WHO Grade IV pineoblastoma. A 13 year old girl with headaches and double vision thought to have right midbrain cavernoma and evaluated at 3 separate institutions was found to have a WHO Grade II diffuse astrocytoma revealed by pathology. Finally, an 8 year old boy thought to have a pontine cavernoma was initially hospitalized for rehabilitation. When neurological symptoms shortly progressed and the lesion was found to double in size radiologically, surgical pathology shown a WHO Grade IV glioblastoma. We present the cases with associated neurological imaging and pathology following surgical biopsy or resection. Often conservative management is indicative for cavernomas based on imaging, but these cases did require surgical procedures given location and symptom control which was necessary to obtain correct diagnosis.